Two-dimensional (2D) graphene nanosheets as advanced lubricant additives: A critical review and prospect. (December 2021) - Zhao, Jun; Gao, Tong; Li, Yingru; He, Yongyong; Shi, Yijun
Abstract: Graphene is a two-dimensional nanomaterial with a monolayer of atomic thickness. Due to its high specific surface area, weak interlayer interaction and good chemical stability, graphene has shown remarkable tribological properties as a lubricant additive. This review focuses on the research progress on graphene-based additives witnessed in recent years. Various synthesis methods of graphene nanomaterials have been displayed, and the review especially highlights the preparation processes of graphene using as a lubricant additive. The dispersion stability of graphene in lubricants is a key concern that has been presented. Besides physical and chemical modifications, a new dispersion method of structural regulation, which has obvious self-dispersed effect, is also discussed in detail. Furthermore, the lubrication mechanisms of graphene additives have been summarized, which will be highly beneficial to optimize the synthesis processes and to regulate the microstructures of graphene for achieving better lubrication. Finally, the challenges and outlook of the future studies on graphene additives are presented in the field of lubrication.